The Equivalence of the Italian and Uzbek Phrase logical Units - Bekhzod Khudaykulov; Fazliddin Abdumalikov (Research Parks Publishing LLC, 2022)
This article is devoted to the study of phrase logical units on the basis of a comparison of the phrase logical units of different languages, including unrelated ones. The research represents the comparative description of the phrase logical units based on the analysis of Italian and Uzbek phraseologisms. The article addresses the comparison of the phrase logical units of different languages and their semantic equivalence in the Italian and Uzbek languages. The article has been analyzed with the help of the continuous sampling and partial selection used for the study of the vocabulary entries from dictionaries in the Italian and Uzbek languages. The phrase logical equivalence is shown in the examples of compared meanings of phrase logical units and grammatical form. Theoretical data about phrase logical units are discussed and analyzed with reasonable examples.